EFFECT OF PROJECTILE NOSE SHAPE ON BALLISTIC RESISTANCE OF THIN POLYCARBONATE PLATE (MT) - HU Jing; ZHANG HanZhe; TIAN Rui; WEI Gang; HU Jian Qiang; DAI FuHong (Jixie qiangdu)
In order to study the influence of warhead shape on the impact performance of polycarbonate（PC） plate against rod projectile, the impact tests of flat-head, hemispherical-head and ogival-head rod projectile with 12.6 mm diameter were carried out by gas gun. The relationship of initial-residual velocity and ballistic limit were obtained, and the deformation and failure mode of PC plate were analyzed in detail. The results show that in the velocity range of 30～120 m/s, the PC plate has the strongest resistance to hemispherical-nosed projectile, followed by flat-nosed projectile, and the weakest resistance to ogival-nosed projectile. The failure modes of PC plate are different after the three kinds of projectiles impact. The plat-bulge and plug failure occur after impacted by flat-nosed projectile, the cap-bulge and petal failure occur after the impact of hemispherical projectile, however, petal failure always occurs after the impact of ogival-nosed projectile. It is found that the energy consumption by crack propagation of PC thin plate is less, and the main reason for the great difference of ballistic performance is the difficulty in producing initial damage of PC plate for different projectiles.